A Study Mechanical Properties for Bark Fiber Reinforced Polyester Composit - Salman, Hann H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Bark fiber has high potential use for composite reinforcement in biocomposite material. The aim of this study is the mechanical properties of Bark fiber reinforced polester composite with varying fiber weight fraction (0% , 5% , 10% , 20%, 30% and 40%) hand lay-up technique which  was used to prepare the composite , specimens for tensile , flexural and impact test according to the ASTM D638 , ASTMD790 , and Iso-179. The over all results showed that  the composite is reinforced with  Bark fiber at weight (10%) higher mechanical properties , and the composite showed improved  mechanical (Flexural).